ASSESSING THE CONTRIBUTION OF TAX REVENUES TO OVERALL ECONOMIC GROWTH EXPANSION IN THE IRAQI ECONOMY DURING THE COURSE OF THE YEARS 1990 - 2020 - Hussein Breesam Habeeb (Scholar Express Journals, 2022)
Taxes have many effects on all aspects of economic and social life, especially their impact on the gross domestic product, and this topic is the focus of the research. The importance of the research lies in knowing the effects caused by tax revenues on economic growth rates in Iraq due to the importance of this resource in contributing to the Iraqi economy and the general budget. One of the problems facing this sector is the decline in these revenues despite the high tax base, as it is assumed that the rise in the tax base will lead to a rise in tax revenues, and thus a high percentage of its contribution to the state’s general budget, which improves the rate of economic growth in any country. The research on this subject aims to know the extent to which tax revenues contribute to raising the rate of economic growth in Iraq during the research period from (1990 - 2020) and to come up with results and recommendations that will improve the level of this resource and the extent of its contribution to supporting other sectors in the environment of the Iraqi economy
Keywords: supporting; resource; contribution; environment